PENCANGKOKAN METIL METAKRILAT PADA KARET ALAM SIKLIS DENGAN INISIATOR DIKUMIL PEROKSIDA: EFEK KONSENTRASI MONOMER - Asmara Sari Nasution; Efi Said; Eddiyanto ,; M. Said Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2014)
The research of grafting methyl methacrylate onto Cyclized Natural Rubber  has been carried out. Dicumyl Peroxide was used as a inisiator and temperature condition at 90oC with variation of time 1 and 2 hours. Grafting process was done with technique of reflux in a tree-neck flask  with condenser and oil bath. Spectra analysis FTIR performed for determine the presence of grafted MMA on the backbone of CNR. The results showed that the product CNR-g-MMA was formed with the marked appearance of the absorption peak wave numbers at 1731 cm-1 (carbonyl group absorption) typical for carbonyl (C = O) of methyl methacrylate. The degree of grafting increased with the increasing time grafting.Keywords: grafting, cyclic natural rubber, mathylmetacrilate, dicumyl peroxide